Cultural Symbolism and Sustainability of Orang Ulu Bead Craft in Bario, Sarawak - Musdi, Shanat; Faridah, Sahari; Shaik Azahar, Shaik Hussain; Jong, Sze Joon (2025)
This paper explores the cultural symbolism, traditional knowledge, and sustainability challenges of bead-making among the Orang Ulu community in Bario, Sarawak. An in-depth interview is conducted with an experienced bead artisan to document the meanings of bead colours and motifs, their traditional functions, and the factors threatening their continuity. Findings reveal that bead colours such as red, white, black, and yellow are imbued with symbolic values representing bravery, purity, ancestral connection, and prosperity. At the same time, motifs depict continuity and wealth. Beads are integral to ceremonial life, social status, and identity affirmation, yet face threats from declining youth participation, scarcity of materials, and competition from mass-produced alternatives. Duxbury et al. (2024) assert that safeguarding such cultural expressions is central to fostering community resilience and resisting the erosion of local identity in the face of globalisation. The study proposes preservation strategies including education-based interventions, modern design collaborations, and community-led exhibitions. These strategies aim to safeguard bead-making as an essential component of intangible cultural heritage, contributing to cultural resilience and sustainable rural development.